Articulating Factors Defining RMS Delay Spread in LV PLC Networks - Sabih Güzelgöz; Hasan Basri Çelebi; Hüseyin Arslan (Journal of Computer Systems, Networks, and Communications)
Communication over the power line network (PLN) referred as power line communication (PLC) has a long history of narrowband applications. With the recent developments in the field of digital communications, current interest is to exploit this medium for wideband communications for several applications such as Internet access, home networking, and in-vehicle data communication. In line with this recently emerging interest which envisions the conversion of a power transmission network into a communication network, understanding the root-mean-squared (RMS) delay spread is essential for multipath PLC channels for the establishment of reliable communication systems. In this paper, factors that play a role on the RMS delay spread value of low voltage (LV) PLC channels are articulated. Among these factors, dependency of the RMS delay spread on attenuation, loading, and physical characteristics of the communication channel in the PLNs is investigated.